An investigation into the contract dispute settlement under security of payment act - Chua, Gim Hock (2014)
The Building and Construction Industry Security of Payment Act came into operation on 1st April 2005. The Act represents the culmination of a remarkable effort on the part of a particular constituency within the construction industry to redress some of the payment issues which have confronted the industry for a long time. For the past 8 years, there were many high profile cases which requires the authority to adjudicate legal disputes between the parties and carry out the administration of justice in accordance with the rule of law. Doubts and questions about certain sections of the SOP Act were gradually cleared up after jurisdiction. In this report, the case between Ssangyong Engineering & Construction Co Ltd and Chip Hup Hup Kee Construction Pte Ltd will be analysed to understand the issues behind the disputes and the reasons behind the court’s decision. In particular, Section 15(3), the Adjudicator’s jurisdiction and the principles of natural justice will be studied thoroughly by the author. Upon finding the pivotal issues of the case, recommendations will be given by the author to allow the Adjudicator to consider some of the suggestions if cases of similar nature were to occur again. Ultimately, the aim of author is to ensure that these valuable lessons learnt will continue to serve the objectives of the SOP Act in improving cash flow by upholding rights of parties to seek progress payment for work done and goods/services supplied and also to provide rapid and low-cost resolution of payment disputes through adjudication.